Smoke Signals: Decoding the Multimodal Strategies of Cigarette Health Warnings in Australia - Halawachy, Huda; Sadallah, Shadha H. (Studies in English Language and Education, 2025)
This study examines the cigarette pack warnings of Australia focusing on how textual and pictorial elements interact to communicate health risks. It identifies the cigarettes companies adopted warning strategies, examines their functions, and investigates how language influences smoker perceptions and behaviours within Australias diverse demographic landscape to optimise health messages for effective tobacco control. This study employed a qualitative design to examine warning strategies and semiotic elements (textual and pictorial) used on Australian cigarette packs. Data embraced health warnings given on seven cigarette packs purposively selected from various brands in Australia, then analyzed according to Kress and van Leeuwens model (2001). The findings revealed a multimodal strategy of warnings on cigarette packs were exploited effectively by incorporating powerful plain texts and pictures to engage the public and smokers in the severe health hazards description. It is through these warnings that the manufacturers aim at, for instance, threatening or advising the Australian smokers to grasp health risks. Worth considering that utilizing vivid symbols, as colours, in health warnings on cigarette packs effectively highlights the severe health risks of smoking, making the dangers more tangible and emotionally compelling for smokers. Recommendations for improving these warnings include enhancing visual impact, using audience-specific messaging, and incorporating easily accessible quit support information. Ongoing updates, legislative support, and complementary public health campaigns are also advised to maintain effectiveness and support broader public health goals against smoking.